Effects of Bacillus Calmette-Guérin on immunometabolism, microbiome and liver diseases - Muhammad Umair Ijaz; Farzam Vaziri; Yu-Jui Yvonne Wan (Liver Research, 2023)
Metabolic diseases have overtaken infectious diseases as the most serious public health issue and economic burden in most countries. Moreover, metabolic diseases increase the risk of having infectious diseases. The treatment of metabolic disease may require a long-term strategy of taking multiple medications, which can be costly and have side effects. Attempts to expand the therapeutic use of vaccination to prevent or treat metabolic diseases have attracted significant interest. A growing body of evidence indicates that Bacillus Calmette-Guérin (BCG) offers protection against non-infectious diseases. The non-specific effects of BCG occur likely due to the induction of trained immunity. In this regard, understanding how BCG influences the development of chronic metabolic health including liver diseases would be important. This review focuses on research on BCG, the constellation of disorders associated with metabolic health issues including liver diseases and diabetes as well as how BCG affects the gut microbiome, immunity, and metabolism.